Convergent correlationism: analyzing teacher educators' reflection on professional practice. Issue 6 (2nd November 2021) - Beighton, Christian
ABSTRACT: This paper uses an original analysis of epistemological presuppositions to develop conclusions about reflective practice in a higher education context. Drawing on interview data and philosopher Quentin Meillassoux's recent work on philosophical presuppositions, I discuss convergence in teachers' 'correlationist' presuppositions about the nature of knowledge and practice. These epistemological presuppositions, which converge around a subjectivist worldview, underpin reflections about pedagogy and can hinder understanding of the limitations and affordances of reflection itself. This analysis leads to three conclusions: first, forms of reflection on practice which seem diverse may converge on essentially similar reflective presuppositions; second, apparent incompatibility between individual examples of reflection about pedagogies can hinder practice where teachers and students fail to perceive this underlying similarity; and third, a scale of comparison (Meillassoux's spectrum) can enhance inclusiveness by identifying where correlationism limits or even forecloses teachers' reflection-on-action.